Changes in Spirituality and the Impact on Mental Health of Canadian Muslim Women in Ottawa - Ansam, Y A Elharan (Université Saint-Paul / Saint Paul University, 2022)
As the population of Muslim women in Canada grows, there is an increasing need for mental health providers who are familiar with the religious and spiritual aspects of Muslim women. Yet psychological research or literature discussing Muslim women clients or their experiences remains scant. The purpose of this research study is to identify the experiences of Canadian Muslim women after occurrences of change in their spirituality, and to observe the impacts on their mental health. This thesis provides some foundational information that mental health providers may consider to work effectively with Muslim women clients. The research illustrates how clinicians can effectively explore and incorporate aspects of Islam in their practice in order to increase their cultural competency when working with Muslim women clients.
Keywords: cultural competency, Canadian mental health providers, psychotherapy, changes in spirituality